Xinli formula’s efficacy in heart failure: analysis via Guangdong TCM hospital database - Cao, Haiming; Zhang, Jiongming; Zhang, Tong; Chen, Xiankun; Liu, Tong; Xu, Wenjing; Zhu, Yi; Jiang, Wei; Lu, Weihui (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the efficacy of the “Xinli Formula” in improving cardiac function, symptoms, and quality of life in patients with heart failure using a hospital database.MethodsA retrospective study included 210 patients (2017–2022) divided into Xinli Formula group (n = 107) and non-Xinli Formula group (n = 103). Outcomes included cardiac function parameters, N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels, 6-min walk distance (6MWD), quality of life (Minnesota Living with Heart Failure Questionnaire, MLHFQ), and inflammatory markers. Data were analyzed using SPSS 26.0.ResultsThe Xinli Formula group showed significant improvements in Left Ventricular Ejection Fractions (LVEF) (38% → 42%), Left Ventricular End-Systolic Diameter (LVESD) (45 mm → 40 mm), Left Ventricular End-Diastolic Diameter (LVEDD) (60 mm → 55 mm), and 6MWD (350 m → 400 m). MLHFQ scores decreased from 45 to 30. Inflammatory markers and NT-proBNP levels also improved significantly.ConclusionThe Xinli Formula significantly improves cardiac function, exercise tolerance, and quality of life in patients with heart failure and may be an effective adjunctive therapy. Further studies are needed.